Measuring Solution Viscosity and its Effect on Enzyme Activity - Uribe Salvador; Sampedro José G. (Biological Procedures Online, 2003)
In proteins, some processes require conformational changes involving structural domain diffusion. Among these processes are protein folding, unfolding and enzyme catalysis. During catalysis some enzymes undergo large conformational changes as they progress through the catalytic cycle. According to Kramers theory, solvent viscosity results in friction against proteins in solution, and this should result in decreased motion, inhibiting catalysis in motile enzymes. Solution viscosity was increased by adding increasing concentrations of glycerol, sucrose and trehalose, resulting in a decrease in the reaction rate of the H+-ATPase from the plasma membrane of Kluyveromyces lactis. A direct correlation was found between viscosity (&eegr;) and the inhibition of the maximum rate of catalysis (V max). The protocol used to measure viscosity by means of a falling ball type viscometer is described, together with the determination of enzyme kinetics and the application of Kramers’ equation to evaluate the effect of viscosity on the rate of ATP hydrolysis by the H+-ATPase.